Adherent cells avoid polarization gradients on periodically poled LiTaO3 ferroelectrics - Christophis, Christof; Cavalcanti-Adam, Elisabetta Ada; Hanke, Maximilian; Kitamura, Kenji; Gruverman, Alexei; Grunze, Michael; Dowben, Peter A.; Rosenhahn, Axel (Biointerphases, 2013)
The response of fibroblast cells to periodically poled LiTaO3 ferroelectric crystals has been studied. While fibroblast cells do not show morphological differences on the two polarization directions, they show a tendency to avoid the field gradients that occur between polarization domains of the ferroelectric. The response to the field gradients is fully established after one hour, a time at which fibroblasts form their first focal contacts. If suspension cells, with a lower tendency to establish strong surface contacts are used, no influence of the field gradients is observed.